EFFECTIVENESS AND DESIGN OF DIGITAL GAME-BASED LEARNING FOR SCIENCE PROCESS SKILLS IN HIGHER EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Rohmani (International Journal of Multidisciplinary Reseach, 2026)
Mastery of Science Process Skills (SPS) is a foundational competency in STEM higher education; however, conventional instructional methods consistently fail to facilitate deep engagement with complex and abstract scientific phenomena. This study aimed to evaluate the effectiveness of Digital Game-Based Learning (DGBL) in developing undergraduate students’ science process skills, and to identify the instructional design elements most critical to achieving these outcomes. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 protocol. Empirical articles were retrieved from Scopus and ScienceDirect (2021–2025) and appraised using the Mixed Methods Appraisal Tool (MMAT). A final corpus of 33 articles was synthesised. DGBL produced consistently positive and significant effects on higher-order science process skills, with synthesised effect sizes of Hedges’ g ≈ 0.65–0.82 for problem-solving, critical thinking, and scientific reasoning. Effects on lower-order skills were more modest (g ≈ 0.38–0.45). Adaptive scaffolding, immediate formative feedback, and precise Learning Mechanics–Game Mechanics (LM–GM) alignment were identified as the most influential design variables. Stealth assessment frameworks provided more objective and process-oriented evaluations than conventional instruments. DGBL grounded in robust pedagogical design effectively bridges the gap between abstract scientific theory and authentic inquiry-based practice. Future research should prioritise Generative AI integration, immersive technologies, and longitudinal studies tracking long-term SPS retention.